2022
DOI: 10.4254/wjh.v14.i4.647
|View full text |Cite
|
Sign up to set email alerts
|

Revolution in the diagnosis and management of hepatitis C virus infection in current era

Abstract: Chronic hepatitis C virus (HCV) infection is a major global public health problem, particularly in developing part of the world. Significant advances have been made in the early diagnosis and treatment of the disease. Its management has been particularly revolutionized during the past two decades. In this review, we summarize the major advances in the diagnostic and management armamentarium for chronic HCV infection. The focus of the present review is on the newer directly acting anti-viral agents, which have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 192 publications
(211 reference statements)
0
2
0
Order By: Relevance
“…Combination therapy of interferon and ribavirin has been used in Pakistan for a long time. For this reason, much research is being done on this topic [11,12]. In recent years, direct-acting antivirals have been just introduced in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy of interferon and ribavirin has been used in Pakistan for a long time. For this reason, much research is being done on this topic [11,12]. In recent years, direct-acting antivirals have been just introduced in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…The Hepatitis C virus (HCV) is a significant issue of public health that impacts 170 million people globally. It represents the most prevalent cause of chronic hepatitis, cirrhosis, and liver cancer worldwide, as well as the principal reason for liver transplants [1,2], and some research revealed that HCV-related mortality (death from liver failure or hepatocellular carcinoma) will keep going up throughout the next couple of decades [3]. Hepatitis C virus (HCV) infection is getting more widespread all over the world.…”
Section: Introductionmentioning
confidence: 99%